The Effectiveness of Card Match Media in Learning Japanese Vocabulary by Islamic Middle School Students at As Shofa Pekanbaru - Arsid, Meisy Sarani; Widiati, Sri Wahyu; Yohani, Adisthi Martha (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Vocabulary is the most important part of learning a language, and is also applied in learning Japanese.  Japanese students face difficulties in learning Japanese vocabulary, therefore teachers are able to provide appropriate media for learning vocabulary.  This study aims to determine the ability to remember and understand Japanese vocabulary of Japanese extracurricular students at As Shofa Islamic Middle School, Pekanbaru, before and after using Card Match as a Japanese language learning medium.  This type of research is quantitative research with a one group pre-test post-test design.  The population in the study were extracurricular Japanese language students at As Shofa Islamic Middle School Pekanbaru, with a sample of 20 students.  The research instrument used in the research was a test consisting of 20 questions.  The results of this research can be seen in the Paired Sample T Test results from the post test value data of 0.001 which shows that Card Match is an effective learning medium to support the ability to remember and understand Japanese vocabulary for Japanese extracurricular students at As Shofa Islamic Middle School Pekanbaru.